Service Quality and Customer Satisfaction at Kenari Hotel Parepare - Mustakim, Hamzah; Putra, Pandi; Natsir, Ulfa (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2020)
This research aims to reveal the effect of service quality, namely physical evidence, reliability, responsiveness, assurance, empathy in creating customer satisfaction. The theory used in this research takes the theory of service marketing management, service quality, customer behavior, customer satisfaction. Samples were taken of 60 respondents and analyzed using multiple linear regression analysis tools, using the SPSS 20 application. The results of the research in this article are related to service quality both partially and simultaneously, which influences customer satisfaction and the result is that the average respondents chose answers to agree and only neutral or quite satisfied.